Nanosilicon-graphite composite negative electrode material having a carbon coating and an aluminum metaphosphate composite modified layer on its surface, and its manufacturing method

The nanosilicon-graphite composite electrode with a carbon and aluminum metaphosphate coating addresses the volume change issues in silicon-based anodes, enhancing cycle stability and conductivity in lithium-ion batteries.

JP2024546517AActive Publication Date: 2024-12-25CHINA NONFERROUS METALS (GUILIN) GEOLOGY AND MINING CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023518905
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-04-29
Filing Date
2022-05-23
Publication Date
2024-12-25
Estimated Expiration
2042-05-23

AI Technical Summary

Technical Problem

Silicon-based anode materials in lithium-ion batteries face significant challenges due to volumetric expansion and contraction, leading to particle powderization, loss of electrical contact, and instability of the SEI membrane, which results in reduced cycle stability and capacity.

Method used

A nanosilicon-graphite composite negative electrode material is developed with a carbon coating and an aluminum metaphosphate composite modification layer, enhancing conductivity and stabilizing the SEI film to accommodate volume changes.

Benefits of technology

The composite material significantly improves cycle life and capacity retention by stabilizing the SEI film and mitigating volume changes, resulting in higher cycle life and improved electrical conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024546517000001_ABST
    Figure 2024546517000001_ABST
Patent Text Reader

Abstract

The present invention relates to a nanosilicon-graphite composite negative electrode material having a carbon coating and an aluminum metaphosphate composite modified layer on the surface and a method for producing the same, which is mainly produced by mass % from 4-10wt.% aluminum metaphosphate, 10wt.% pitch decomposition carbon, 15wt.% spherical nanosilicon powder, and 71-65wt.% graphite powder, and the nanosilicon powder is added to deionized water and ultrasonically dispersed, and then graphite powder is added and uniformly ultrasonically stirred, and then aqueous asphalt is added and uniformly stirred and mixed, and then spray dried, and the dried powder is combined with metaphosphate and mechanically fused, and finally transferred to a vacuum furnace for high-temperature carbonization. The present invention discloses a nanosilicon-graphite composite negative electrode material having a carbon coating and an aluminum metaphosphate composite modified layer, and the composite modified layer on the surface can effectively inhibit the corrosion of the nanosilicon material by the electrolyte, mitigate the volume expansion, improve the electrical conductivity, and improve the cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the technical field of electrochemical power supply, in particular to a nanosilicon-graphite composite negative electrode material having a carbon coating and an aluminum metaphosphate composite modification layer on its surface, and a method for preparing the same. [Background technology]

[0002] Silicon absorbs lithium by forming a lithium-silicon alloy with lithium, but the lithium absorption process is accompanied by a huge volume expansion, and the lithium de-alloying process is accompanied by a severe volume contraction. This volume change is as large as 300%, which is very easy to cause silicon material powdering and seriously affect the cycle stability. Although the particle powdering of silicon material in the electrochemical cycle process can be effectively solved by producing nanosilicon powder with appropriate particle size, the huge volume change effect still exists after lithium absorption in nanosilicon material, and when the electrode repeats volume expansion and contraction, the particles still lose electrical contact and powdering, resulting in capacity loss and cycle life attenuation. It is an effective and feasible low-cost method to obtain a new composite anode material that compensates for the inherent shortcomings of silicon-based materials and meets the specific capacity and cycle life demands of lithium-ion battery anode materials by compounding nanosilicon materials on the traditional mature commercial graphite-based anode material as the framework.

[0003] However, when nanosilicon and graphite are combined, the expansion and contraction rates of the two when releasing and absorbing lithium do not match, so that the nanosilicon particles lose electrical contact, which is likely to result in loss of capacity, and the SEI film formed on the surface becomes unstable, which causes the electrolyte to be constantly consumed and inhibits the transmission of lithium ions in the battery, thereby reducing the cycle life of the material. Furthermore, at this stage, the cycle life is mainly improved by nano-sizing the silicon material and combining it with other materials. However, when the silicon material is nano-sized, the specific surface area is large, the surface is easily eroded by the electrolyte, and even when the silicon material is nano-sized, there is still expansion due to lithium absorption, so further surface modification is required. The present invention obtains a nanosilicon-graphite composite negative electrode material with a long cycle life by performing carbon coating and metaphosphate composite modification on the surface of the material in a simple manner. Summary of the Invention

[0004] In view of this, an object of the present invention is to provide a nanosilicon-graphite composite negative electrode material having a carbon coating and an aluminum metaphosphate composite modified layer on its surface, and a method for producing the same.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions.

[0006] A nanosilicon-graphite composite negative electrode material having a carbon coating and an aluminum metaphosphate composite modification layer on its surface, the negative electrode material mainly comprising: It is produced from the following components (by mass): 4-10 wt.% aluminum metaphosphate, 10 wt.% pitch decomposition carbon, 15 wt.% spherical nanosilicon powder, and 71-65 wt.% graphite powder.

[0007] Another technical object of the present invention is to provide a method for producing the above-mentioned nanosilicon-graphite composite negative electrode material having a carbon coating and an aluminum metaphosphate composite modified layer on the surface thereof, including a method and steps for producing the surface carbon coating and the aluminum metaphosphate composite modified layer, the nanosilicon-graphite composite material, and using it as a silicon carbon composite material for lithium ion batteries, where the method for producing the nanosilicon-graphite composite material is as follows:

[0008] First, the nanosilicon powder is added to deionized water and ultrasonically dispersed to obtain a uniform dispersion, then graphite powder is added and uniformly ultrasonically stirred, then aqueous asphalt is added and uniformly stirred and mixed, then spray-dried, the dried powder is combined with metaphosphate and mechanically fused, and finally transferred to a vacuum furnace for high-temperature carbonization to obtain a nanosilicon-graphite composite negative electrode material having a carbon coating and an aluminum metaphosphate composite modification layer on the surface.

[0009] in particular, Step 1) weighing nanosilicon powder according to the formula, adding it to deionized water, and dispersing it by ultrasonic stirring to obtain a nanosilicon powder dispersion; Step 2) is to stir the suspension of step 1 at high speed, add graphite powder according to the mixing ratio, and add aqueous asphalt after stirring and mixing for a certain period of time. The mixture is then stirred uniformly at high speed while adding deionized water to control the solid content of the suspension to within the range of 10 to 15 wt.%. Step 3) of spray-drying the suspension of step 2) in a spray dryer, controlling the spray inlet temperature at 200-220°C and the feed rate at 20-30 kg / h to obtain a dry powder; Step 4) weighing out aluminum metaphosphate powder according to the blending ratio, adding it to the dry powder of step 3), mixing it uniformly, and then adding it to a mechanical blender for blending to obtain a precursor having asphalt and aluminum metaphosphate modified layers coated on the surface; The precursor in step 4) is transferred to a vacuum furnace for high-temperature carbonization at 800-1200°C for 3-6 h, and then taken out, crushed and sieved to obtain a nanosilicon-graphite composite negative electrode material having a carbon coating and an aluminum metaphosphate composite modification layer on its surface.

[0010] It should be explained that the present invention uses the carbon coating layer modification on the surface of the nanosilicon-graphite composite anode material to effectively improve the bonding strength between nanosilicon and graphite, and improve the electrical conductivity of the silicon material, and the aluminum metaphosphate modification on the surface effectively alleviates the volume expansion and stabilizes the SEI film formed on the surface of the material. The present invention uses the carbon coating and aluminum metaphosphate composite modification layer on the surface to manufacture the nanosilicon-graphite composite anode material, and then uses the carbon coating and aluminum metaphosphate composite modification layer on the surface to reinforce the electrical conductivity of the nanosilicon particles, stabilize the SEI film, and alleviate the volume change of the material, thereby obtaining a composite anode material with a longer cycle life.

[0011] Compared with the prior art, the present invention discloses a nanosilicon-graphite composite negative electrode material having a carbon coating and an aluminum metaphosphate composite modified layer on its surface and a manufacturing method thereof, which has the following beneficial effects:

[0012] 1) The presence of the composite modification layer not only has the same effects as the conventional carbon coating, such as improving the electrical conductivity of the silicon material, blocking the erosion of the silicon material by the electrolyte, and mitigating volume expansion, but also the dispersion of aluminum metaphosphate in the coating layer can reinforce the peel strength of the coating layer and better adapt to the volume change of the material.

[0013] 2) The presence of aluminum metaphosphate forms a stable SEI film on the surface of the material, reducing electrolyte consumption and contributing to a higher cycle life. [Brief description of the drawings]

[0014] In order to more clearly describe the technical solutions in the embodiments of the present invention or the prior art, the following briefly introduces drawings that need to be used in the embodiments or prior art description. It is obvious that the drawings in the following description are only the embodiments of the present invention, and those skilled in the art can derive other drawings from the drawings provided without exerting any creative efforts. [Figure 1]1 is an energy spectrum analysis of the nanosilicon-graphite composite negative electrode material with aluminum metaphosphate modification on the surface prepared according to the present invention; [Diagram 2] FIG. 2 is a capacity retention curve obtained by assembling the silicon carbon composite materials prepared in Example 1 and Comparative Example 1 of the present invention as negative electrodes into 2032 button batteries and then testing them. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The following clearly and completely describes the technical solutions in the embodiments of the present invention in conjunction with the specification and drawings, and obviously, the described embodiments are only some of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained based on the embodiments of the present invention without the creative efforts of those skilled in the art are all within the scope of protection of the present invention.

[0016] The present invention discloses and protects a method for preparing a nanosilicon-graphite composite negative electrode material having a carbon coating and an aluminum metaphosphate composite modification layer on its surface.

[0017] The technical solution of the present invention will be further described below in conjunction with specific examples, but the content of the present invention is not limited to the following examples. EXAMPLES

[0018] A method for producing a nanosilicon-graphite composite negative electrode material having a carbon coating and an aluminum metaphosphate composite modification layer on its surface, comprising the steps of: Step 1) weigh out 450 g of nanosilicon powder, add it to 27 kg of deionized water, and disperse it by ultrasonic stirring to obtain a suspension of nanosilicon powder; Step 2) While stirring the suspension from step 1 at high speed, add 1950 g of graphite powder, stir thoroughly to mix uniformly, add 1200 g of water-based asphalt (solid content 50 wt.%, vacuum carbonization residual carbon content 50 wt.%), mix uniformly, and obtain a uniform slurry with a solid content of about 10 wt.%. Step 3) of spray-drying the uniform slurry obtained in step 2) while ultrasonically stirring the mixture, controlling the sprayer inlet temperature at 220°C and the feed rate at 30 kg / h to obtain a dry powder; Step 4) weigh out 300 g of aluminum metaphosphate powder and add it to a mechanical fusion machine together with the dried powder obtained in step 3), and extrude at high speed for 20 minutes to fuse them together to obtain a precursor having asphalt and aluminum metaphosphate modified layers coated on the surface; Step 5) of transferring the precursor in step 4) to a vacuum furnace and carbonizing it under vacuum conditions at 800°C for 3 hours to carbonize the pitch at high temperature, thereby obtaining a nanosilicon-graphite composite negative electrode material having about 10 wt.% pitch decomposition carbon and 10 wt.% aluminum metaphosphate composite modification layer on the surface; The nanosilicon-graphite composite negative electrode material prepared in this embodiment was manufactured into a negative electrode plate, which was then assembled into a 2032 button battery to carry out a cycle life test. The material performance data is shown in Table 1, and the cycle life curve is shown in FIG.

[0019] Here, the method for testing the battery cycle performance is to first discharge the battery to 0.01 V at a current density of 100 mA / g, then further discharge the battery to 0.005 V at a current of 10 mA / g, leave the battery to stand for 3 minutes, and then charge the battery to 1.5 V at a current density of 100 mA / g, which constitutes one cycle, and then perform the cycle performance test.

[0020] The nanosilicon-graphite composite negative electrode material with aluminum metaphosphate modification on the surface produced by the present invention is specifically subjected to energy spectrum analysis as shown in Figure 1. As can be seen from the energy spectrum diagram, nanosilicon particles are dispersed on the surface of the graphite particles in the composite material, and the particles are bound into a whole by the carbon coating on the surface and the aluminum metaphosphate modification layer. EXAMPLES

[0021] A method for producing a nanosilicon-graphite composite negative electrode material having a carbon coating and an aluminum metaphosphate composite modification layer on its surface, comprising the steps of: Step 1) weigh out 450 g of nanosilicon powder, add it to 27 kg of deionized water, and disperse it by ultrasonic stirring to obtain a suspension of nanosilicon powder; Step 2) is to add 2130 g of graphite powder while stirring the suspension from step 1 at high speed, and mix thoroughly to homogeneously. Then, add 1200 g of water-based asphalt (solid content 50 wt.%, vacuum carbonization residual carbon content 50 wt.%) and mix homogeneously to obtain a homogeneous slurry with a solid content of about 10 wt.%. Step 3) of spray-drying the uniform slurry obtained in step 2) while ultrasonically stirring the mixture, controlling the sprayer inlet temperature at 200°C and the feed rate at 30 kg / h to obtain a dry powder; Step 4) weigh out 120 g of aluminum metaphosphate powder and add it to a mechanical fusion machine together with the dried powder obtained in step 3), and extrude at high speed for 20 minutes to fuse them together to obtain a precursor having asphalt and aluminum metaphosphate modified layers coated on the surface; The precursor in step 4) is transferred to a vacuum furnace and carbonized for 6 hours under vacuum conditions at 800°C, thereby carbonizing the pitch at high temperature and obtaining a nanosilicon-graphite composite negative electrode material having about 10 wt.% pitch decomposition carbon and 4 wt.% aluminum metaphosphate composite modification layer on the surface. EXAMPLES

[0022] A method for producing a nanosilicon-graphite composite negative electrode material having a carbon coating and an aluminum metaphosphate composite modification layer on its surface, comprising the steps of: Step 1) weigh out 450 g of nanosilicon powder, add it to 17 kg of deionized water, and disperse it by ultrasonic stirring to obtain a suspension of nanosilicon powder; Step 2) While stirring the suspension from step 1 at high speed, add 1950 g of graphite powder, stir thoroughly to mix uniformly, add 1200 g of water-based asphalt (solid content 50 wt.%, vacuum carbonization residual carbon content 50 wt.%), mix uniformly, and obtain a uniform slurry with a solid content of about 15 wt.%. Step 3) of spray-drying the uniform slurry obtained in step 2) while ultrasonically stirring the mixture, controlling the sprayer inlet temperature at 200°C and the feed rate at 30 kg / h to obtain a dry powder; Step 4) weigh out 300 g of aluminum metaphosphate powder and add it to a mechanical fusion machine together with the dried powder obtained in step 3), and extrude at high speed for 20 minutes to fuse them together to obtain a precursor having asphalt and aluminum metaphosphate modified layers coated on the surface; The precursor in step 4) is transferred to a vacuum furnace and carbonized for 6 hours under vacuum conditions at 1000°C, thereby carbonizing the pitch at high temperature and obtaining a nanosilicon-graphite composite negative electrode material having about 10 wt.% pitch decomposition carbon and 10 wt.% aluminum metaphosphate composite modification layer on the surface. EXAMPLES

[0023] A method for producing a nanosilicon-graphite composite negative electrode material having a carbon coating and an aluminum metaphosphate composite modification layer on its surface, comprising the steps of: Step 1) weigh out 450 g of nanosilicon powder, add it to 22 kg of deionized water, and disperse it by ultrasonic stirring to obtain a suspension of nanosilicon powder; Step 2) While stirring the suspension from step 1 at high speed, add 2010 g of graphite powder, stir thoroughly to mix uniformly, add 1200 g of water-based asphalt (solid content 50 wt.%, vacuum carbonization residual carbon content 50 wt.%), and mix uniformly to obtain a uniform slurry with a solid content of about 12.2 wt.%. Step 3) of spray-drying the uniform slurry obtained in step 2) while ultrasonically stirring the mixture, controlling the sprayer inlet temperature at 210°C and the feed rate at 30 kg / h to obtain a dry powder; Step 4) weigh out 240 g of aluminum metaphosphate powder and add it to a mechanical fusion machine together with the dried powder obtained in step 3), and extrude at high speed for 20 minutes to fuse them together to obtain a precursor having asphalt and aluminum metaphosphate modified layers coated on the surface; The precursor in step 4) is transferred to a vacuum furnace and carbonized under vacuum conditions at 1200°C for 3 hours, and step 5) carbonizes the pitch at high temperature to obtain a nanosilicon-graphite composite negative electrode material having about 10 wt.% pitch decomposition carbon and 8 wt.% aluminum metaphosphate composite modification layer on the surface. EXAMPLES

[0024] A method for producing a nanosilicon-graphite composite negative electrode material having a carbon coating and an aluminum metaphosphate composite modification layer on its surface, comprising the steps of: Step 1) weigh out 450 g of nanosilicon powder, add it to 27 kg of deionized water, and disperse it by ultrasonic stirring to obtain a suspension of nanosilicon powder; Step 2) is to add 2070 g of graphite powder while stirring the suspension from step 1 at high speed, and mix thoroughly to mix uniformly. Then, add 1200 g of water-based asphalt (solid content 50 wt.%, vacuum carbonization residual carbon content 50 wt.%) and mix uniformly to obtain a uniform slurry with a solid content of about 10.4 wt.%. Step 3) of spray-drying the uniform slurry obtained in step 2) while ultrasonically stirring the mixture, controlling the sprayer inlet temperature at 220°C and the feed rate at 30 kg / h to obtain a dry powder; Step 4) weigh out 180 g of aluminum metaphosphate powder and add it to a mechanical fusion machine together with the dried powder obtained in step 3), and extrude and fuse at high speed for 20 minutes to obtain a precursor having asphalt and aluminum metaphosphate modified layers coated on the surface; The precursor in step 4) is transferred to a vacuum furnace and carbonized under vacuum conditions at 1100°C for 4 hours, and step 5) carbonizes the pitch at high temperature to obtain a nanosilicon-graphite composite negative electrode material having about 10 wt.% pitch decomposition carbon and 6 wt.% aluminum metaphosphate composite modification layer on the surface.

[0025] In order to further verify the superior effects of the present application compared with the prior art, the inventors further conducted the following comparative experiments and performance tests, the specific contents of which are as follows: Comparative Example 1

[0026] 1) Weigh out 450 g of nanosilicon powder, add it to 27 kg of deionized water, and disperse it by ultrasonic stirring to obtain a suspension of nanosilicon powder; 2) While stirring the suspension of step 1) at high speed, add 1950 g of graphite powder and stir thoroughly to mix uniformly. Then add 1200 g of water-based asphalt (solid content 50 wt.%, vacuum carbonization residual carbon content 50 wt.%) and mix uniformly to obtain a uniform slurry with a solid content of about 10 wt.%. 3) The uniform slurry obtained in step 2) is spray-dried under ultrasonic stirring, and the sprayer inlet temperature is controlled at 220°C and the feed rate is controlled at 30 kg / h to obtain a dry powder; 4) The precursor in step 3) is transferred to a vacuum furnace and carbonized under vacuum conditions at 800 ° C for 3 h to carbonize the pitch at high temperature, obtaining a nanosilicon-graphite composite negative electrode material having only a carbon coating layer on the surface and no aluminum metaphosphate modification; The nanosilicon-graphite composite anode material without surface modification in Comparative Example 1 was assembled into a 2032 button battery to carry out a cycle life test. The material performance data is shown in Table 1, and the cycle life curve is shown in Figure 2. Comparative Example 2

[0027] 1) Weigh out 450 g of nanosilicon powder, add it to 27 kg of deionized water, and disperse it by ultrasonic stirring to obtain a suspension of nanosilicon powder; 2) While stirring the suspension of step 1) at high speed, add 1950 g of graphite powder and stir thoroughly to mix uniformly. Then add 1200 g of water-based asphalt (solid content 50 wt.%, vacuum carbonization residual carbon content 50 wt.%) and mix uniformly to obtain a uniform slurry with a solid content of about 10 wt.%. 3) The uniform slurry obtained in step 2) is spray-dried under ultrasonic stirring, and the sprayer inlet temperature is controlled at 220°C and the feed rate is controlled at 30 kg / h to obtain a dry powder; 4) The precursor in step 3) is transferred to a vacuum furnace and carbonized under vacuum conditions at 800 ° C for 3 h, so that the pitch is carbonized at high temperature to obtain a nanosilicon-graphite composite negative electrode material with no carbon coating layer on the surface and only aluminum metaphosphate modification; The nanosilicon-graphite composite anode material without surface modification in Comparative Example 2 was assembled into a 2032 button battery and subjected to cycle life testing, and the material performance data are shown in Table 1. Comparative Example 3

[0028] 1) Weigh out 450 g of nanosilicon powder, add it to 27 kg of deionized water, and disperse it by ultrasonic stirring to obtain a suspension of nanosilicon powder; 2) While stirring the suspension of step 1) at high speed, add 1950 g of graphite powder and stir thoroughly to mix uniformly to obtain a uniform slurry with a solid content of about 10 wt.%. 3) The uniform slurry obtained in step 2) is spray-dried under ultrasonic stirring, and the sprayer inlet temperature is controlled at 220°C and the feed rate is controlled at 30 kg / h to obtain a dry powder; 4) The precursor in step 3) is transferred to a vacuum furnace and carbonized under vacuum conditions at 800 °C for 3 h to obtain a nanosilicon-graphite composite anode material with no carbon coating or aluminum metaphosphate modification on the surface; The nanosilicon-graphite composite negative electrode material without surface modification in Comparative Example 3 was assembled into a 2032 button battery and subjected to a cycle life test. The material performance data are shown in Table 1.

[0029] As can be seen from Table 1, in Comparative Example 3 without surface modification, the capacity retention rate after 300 cycles is only 28.4%, in Comparative Example 1 with only carbon coating layer modification, the capacity retention rate after 300 cycles is 70.7%, and in Comparative Example 2 with only aluminum metaphosphate modification, the capacity retention rate after 300 cycles is 46.2%. However, after carbon coating and aluminum metaphosphate composite modification, the cycle life of the material is significantly improved, and the capacity retention rates after 300 cycles of the samples in Examples 1 to 5 are 103.7%, 87.8%, 104.3%, 102.8% and 104.4%, respectively. Through comparative analysis, it is found that the carbon coating and aluminum metaphosphate composite modification layer designed in the present invention can significantly improve the cycle life of the nanosilicon-graphite composite negative electrode material.

[0030] [Table 1]

[0031] The above description of the disclosed embodiments enables those skilled in the art to realize or use the present invention. Various modifications of these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention is not limited to these embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A nanosilicon-graphite composite negative electrode material having a carbon coating and an aluminum metaphosphate composite modification layer on its surface, the negative electrode material mainly comprising: A nanosilicon-graphite composite negative electrode material having a carbon coating and an aluminum metaphosphate composite modification layer on its surface, characterized in that the material is produced from components in mass % of 4-10 wt. % aluminum metaphosphate, 10 wt. % pitch decomposition carbon, 15 wt. % spherical nanosilicon powder, and 71-65 wt. % graphite powder.

2. A method for producing a nanosilicon-graphite composite negative electrode material having a carbon coating and an aluminum metaphosphate composite modified layer on the surface thereof according to claim 1, comprising the steps of: Step 1) weighing nanosilicon powder according to the formula, adding it to deionized water, and dispersing it by ultrasonic stirring to obtain a nanosilicon powder dispersion; Step 2) of stirring the suspension of step 1 at high speed, adding graphite powder according to the mixing ratio, stirring and mixing for a certain period of time, adding water-based asphalt, stirring uniformly at high speed, and adding deionized water to control the solid content of the suspension within the range of 10 to 15 wt. %; Step 3) of spray drying the suspension of step 2) in a spray dryer to obtain a dry powder; Step 4) weighing aluminum metaphosphate powder according to the blending ratio, adding it to the dry powder of step 3), mixing uniformly, and then adding it to a mechanical blender for blending to obtain a precursor having asphalt and aluminum metaphosphate modified layer coated on the surface; and step 5) of subjecting the precursor in step 4) to high temperature carbonization in a vacuum furnace, and then removing, crushing and sieving the precursor to obtain a nanosilicon-graphite composite negative electrode material having a carbon coating and an aluminum metaphosphate composite modified layer on its surface.

3. The method for producing a nanosilicon-graphite composite negative electrode material having a carbon coating and an aluminum metaphosphate composite modified layer on its surface, as described in claim 2, characterized in that in step 3), the spray inlet temperature is 200-220°C, and the supply rate is 20-30 kg / h.

4. The method for producing a nanosilicon-graphite composite negative electrode material having a carbon coating and an aluminum metaphosphate composite modified layer on its surface, as described in claim 2, characterized in that in step 5), the high-temperature carbonization temperature is 800-1200°C, and the carbonization time is 3-6h.

Citation Information

Patent Citations

  • Preparation method of high-capacity silicon-based negative electrode material of lithium-ion battery

    CN106025211A

  • Silicon-carbon composite negative pole material preparation method and lithium ion battery

    CN106257716A

  • High-conductivity silicon-oxygen negative electrode material and application thereof

    CN111048756A

  • Negative electrode material for lithium batteries and preparation method thereof

    CN112133894A

  • Slurry-stable lithiated silicon-based composite material as well as preparation method and application thereof

    CN113437280A